1990
DOI: 10.4141/cjas90-079
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dietary Methionine and Lysine on Broiler Chicken Performance and Breast Meat Yield

Abstract: For personal use only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
62
2
17

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(91 citation statements)
references
References 5 publications
(1 reference statement)
9
62
2
17
Order By: Relevance
“…The interaction effects of dLys × dMet was significant for BM model, whereas the interaction effects of dLys × dThr was significant for LM model. Hickling et al (1990) and Kidd et al (1997) also found the significant effects of dLys × dMet for optimizing carcass yield. However, the significant effects of dLys × dThr for optimizing thigh meat yield has been reported (Kidd et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The interaction effects of dLys × dMet was significant for BM model, whereas the interaction effects of dLys × dThr was significant for LM model. Hickling et al (1990) and Kidd et al (1997) also found the significant effects of dLys × dMet for optimizing carcass yield. However, the significant effects of dLys × dThr for optimizing thigh meat yield has been reported (Kidd et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In such experiments, the single nutrient input approach and simple regression does not completely take into account the basic knowledge behind nutrition including intricate relationships between amino acids (De Leon et al, 2010;Mehri et al, 2012). Although traditional factorial designs can be used to test interactions among dietary nutrients (Hickling et al, 1990;Kidd et al, 1997), such factorial designs cannot efficiently identify curvature among multiple independent variables. Therefore, optimal experimental designs should be employed to model these curvatures to define a combination of dietary amino acids describing the most desirable response in growth rate (De Leon et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Menurut Rizkuna et al (2014) lisin sangat berkaitan dengan proses pertumbuhan sel tulang, Ca dibantu oleh protein dan lisin dalam proses penyerapan kemudian dimanfaatkan untuk pembentukan tulang. Menurut Hickling et al (1990) penambahan lisin dan methionin dapat meningkatkan bobot dada.…”
Section: Pengaruh Perlakuan Terhadap Bobot Potongan Karkasunclassified
“…A diversidade de informações exige cautela na análise dos objetivos e das particu-1092 BARBOZA et al laridades em que os dados de cada trabalho são coletados. Em geral, verificam-se consideráveis variações quanto aos valores de exigência de metionina (JENSEN et al, 1989;HICKLING et al, 1990) e lisina (AL-NASSER et al, 1986) para frangos de corte. Por isso, a determinação das exigências nutricionais destes aminoácidos para frangos de corte ainda é fator de grande importância para a moderna avicultura industrial.…”
Section: Introductionunclassified